2016
DOI: 10.1017/s1759078716000076
|View full text |Cite
|
Sign up to set email alerts
|

Neurospectral computation for the resonant characteristics of microstrip patch antenna printed on uniaxially anisotropic substrates

Abstract: Modeling and design of rectangular microstrip patch printed on isotropic or anisotropic substrate are accomplished in this paper. The use of spectral domain method in conjunction with artificial neural networks (ANNs) to compute the resonant characteristics of rectangular microstrip patch printed on isotropic or anisotropic substrates. The moment method implemented in the spectral domain offers good accurateness, but its computational cost is high owing to the evaluation of the slowly decaying integrals and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As seen in Figure 5 and Figure 6, while the harmony is high at low frequencies, the discrepancy between the estimated data and the simulation data increases as the frequency increases. As mentioned in the literature review, most of the studies related to CCMAs have focused on optimizing the antenna designs for specific applications and obtaining mathematical models that usually provide the resonant frequency [3,5,6,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Although this study is not directly related to the estimation of resonant frequencies of CCMAs, the resonant frequencies in dominant mode (TM010) were indirectly estimated by the interpretation of the S11 curves, and the comparison between the results obtained in this study and the results in the literature [7,23] is shown in Table 5.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As seen in Figure 5 and Figure 6, while the harmony is high at low frequencies, the discrepancy between the estimated data and the simulation data increases as the frequency increases. As mentioned in the literature review, most of the studies related to CCMAs have focused on optimizing the antenna designs for specific applications and obtaining mathematical models that usually provide the resonant frequency [3,5,6,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Although this study is not directly related to the estimation of resonant frequencies of CCMAs, the resonant frequencies in dominant mode (TM010) were indirectly estimated by the interpretation of the S11 curves, and the comparison between the results obtained in this study and the results in the literature [7,23] is shown in Table 5.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…In recent years, researchers have vigorously challenged the accurate calculation of the resonant frequency of CMAs. While most studies focus on designing and optimizing CMA structures [3,[17][18][19][20] and obtaining mathematical models for determining the resonant frequencies of the antennas [5,7,[21][22][23][24], there are also studies on computing the resonant frequencies or other characteristic parameters using neural network models [25][26][27][28][29][30][31][32][33][34]. In most recent studies, resonant frequency estimation was made in two ways: the closed-form expression approach and the neural model approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations